The Unlucky Lottery Winners of Classroom 13 - Lee, Honest; Gilbert, Matthew J.; Dreidemy, Joelle (New York ; Little, Brown and Company, 2017)
"Unlucky teacher Ms. Linda LaCrosse wins the lottery and shares her winnings with her class. The students fulfill their dreams with their newfound wealth, but they soon learn that winning the lottery is not all that lucky"--
Keywords: Luck -- Fiction; Lotteries -- Fiction; Schools -- Fiction; Humorous Stories; Luck -- Juvenile fiction; Lotteries -- Juvenile fiction; Schools -- Juvenile fiction; Humorous Stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Readers / Chapter Books